PEMIKIRAN PENDIDIKAN KH. HASYIM ASY’ARI (Studi Kompetensi Kepribadian Guru dalam Kitab Adab al-‘alim wa al-muta’allim): PEMIKIRAN PENDIDIKAN KH. HASYIM ASY’ARI (Studi Kompetensi Kepribadian Guru dalam Kitab Adab al-‘alim wa al-muta’allim) - Muhammad Zaim (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
In general, character education now is still at the level of memorization and/or introduce a value but has not reached the appreaciationof values level, even it makes a personal commitment in life. Therefore, it is requiring in-depth review of the educational character from some classical and modern literature that will contribute to such thinking. If we review the book Adab al-'Alim wa al-Muta'allim work of K.H. Hasyim Asy’ari, there is a treatise on education that includes character education, especially about the competency attitude values that should be owned by educators. And the relevance of competency attitude education by K.H. Hasyim Asy’ari in the context competency attitude education in Indonesia includes several components of character education. Starting from the above problems, it becomes urgent to do this research. The focus of this study, how does a competency attitude educator by K.H. Hasyim Asy’ari? And how relevance of competency attitude education by K.H. Hasyim Asy’ari in the context competency attitude education in Indonesia.